Systemic Mesenchymal Stem Cell-Derived Exosomes Reduce Myocardial Infarct Size: Characterization With MRI in a Porcine Model - Charles, Christopher J.; Li, Renee R.; Yeung, Teresa; Mazlan, Stephane M. Ibraham; Lai, Ruenn Chai; de Kleijn, Dominique P. V.; Lim, Sai Kiang; Richards, A. Mark (Frontiers in Cardiovascular Medicine, 2020)
The observations that mesenchymal stem cells (MSCs) exert cardiac protection and repair via their secretome with the active component(s) identified as exosomes underpinned our test of the efficacy of MSC exosomes in a porcine model of myocardial infarction (MI) when administered systemically by the convenient method of intravenous (IV) bolus injection. Results show that 7 days of IV exosomes results in clear reduction (30-40%) of infarct size measured at both 7 and 28 days post-MI, despite near identical release of hs Troponin T. Together with reduced infarct size, exosome treatment reduced transmurality and lessened wall thinning in the infarct zone. Exosome treated pigs showed relative preservation of LV function with significant amelioration of falls in fractional wall thickening compared with control. However, global measures of LV function were less protected by exosome treatment. It is possible that greater preservation of global LV function may have been attenuated by increased cardiac fibrosis, as T1 values showed significant increase in the exosome pigs compared to control particularly in the infarct related segments. Taken together, these results show clear effects of IV exosomes administered over 7 days to reduce infarct size with relatively preserved cardiac function compared to control treated infarct pigs.